Evolving trends in lung cancer risk factors in the ten most populous countries: an analysis of data from the 2019 Global Burden of Disease StudyResearch in context - Chinmay T. Jani; Samuel A. Kareff; Dan Morgenstern-Kaplan; Ana S. Salazar; Georgina Hanbury; Justin D. Salciccioli; Dominic C. Marshall; Joseph Shalhoub; Harpreet Singh; Estelamari Rodriguez; Gilberto Lopes (EClinicalMedicine)
Summary: Background: Amid shifting tobacco policies and escalating air pollution levels, Lung Cancer (LC) risk factors have changed notably. Continuous assessment of these risk factors is necessary. This study compares trends in tobacco, air pollution, and asbestos-associated Age-Standardized Mortality Rates (ASMR) from Trachea, Bronchus, and Lung (TBL) Cancer across the top ten most populated countries (2023 censuses) and globally. Methods: We extracted overall and risk-factor-associated TBL cancer ASMR of the ten most populated countries for 1990–2019 from the Global Burden of Disease (GBD) database using the dedicated results tool (http://ghdx.healthdata.org/gbd-results-tool). GBD mapped the mortality data related to ICD codes (C33–C34, D02.1-D02.2, D38.1, 162–162.9, 231.1, 231.2, 231.8, 235.7 from ICD10 and B101 from ICD9). Tobacco, occupational exposure to asbestos and air pollution (ambient particulate matter and household air pollution) associated TBL cancer mortality data were extracted to evaluate the trends based on risk factors. We calculated relative changes in ASMRs between 1990 and 2019 for each sex in each country for each risk factor. Joinpoint regression analysis was performed to calculate the Estimated Annual Percentage Change (EAPC) and its corresponding 95% confidence interval (CI) for each line segment, allowing for trend assessment. Findings: Globally, TBL Cancer mortality has decreased by 8%, with a decrease for males but an increase for females. Globally, both tobacco and air pollution-associated TBL cancer ASMR have decreased. While tobacco-associated ASMR has increased in China and Indonesia, air pollution-associated ASMR has also increased in China, India, Pakistan, and Nigeria. On stratification, while PM-associated mortality increased by 25% globally, household-associated TBL cancer ASMR decreased by 62%. China had the highest PM-associated TBL Cancer in 2019 (8.8/100,000), twice higher than the global average. Despite a decline in asbestos-associated TBL cancer ASMR from 8.91/100,000 to 6.0/100,000, the rate in the United States remained twice higher than the global average for the entire study period. Interpretation: Tobacco-associated TBL cancer mortality is declining but still predominant. Ambient particulate matter-associated TBL cancer mortality is rising, requiring policy and awareness efforts. Expanding access to preventive services and addressing underlying risk factors are essential steps required toward reducing lung cancer mortality at the global level. Funding: This study did not receive any funding support.